Epidural hematoma in newborn: literature review - Isabela do Prado Nascimento; Gabriela Ferreira Kalkmann; Leticia Adrielle dos Santos; Letícia Novak Crestani; Carlos Umberto Pereira (Brazilian Society for Pediatric Neurosurgery, 2020)
Introduction: Newborn represent a population at high risk for brain damage. Intracranial hemorrhages in newborn are uncommon, and epidural hematoma (EH) is rare. Material and methods: The authors present a literature review about EH in newborn. Results: EH in newborn occurs in only 2% and is frequently associated with the type of delivery. The clinical presentation is asymptomatic or heterogeneous. The diagnosis is made from anamnesis and imaging exams, and the treatment depends on the size of the EH. Conclusion: The knowledge of neurosurgeons, obstetricians and pediatricians about the occurrence of EH in newborn is extremely important. The rapid identification and management of the case is of paramount importance, to reduce neurological sequelae.